6x-4y+5z=27

Simple and best practice solution for 6x-4y+5z=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-4y+5z=27 equation:


Simplifying
6x + -4y + 5z = 27

Solving
6x + -4y + 5z = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4y' to each side of the equation.
6x + -4y + 4y + 5z = 27 + 4y

Combine like terms: -4y + 4y = 0
6x + 0 + 5z = 27 + 4y
6x + 5z = 27 + 4y

Add '-5z' to each side of the equation.
6x + 5z + -5z = 27 + 4y + -5z

Combine like terms: 5z + -5z = 0
6x + 0 = 27 + 4y + -5z
6x = 27 + 4y + -5z

Divide each side by '6'.
x = 4.5 + 0.6666666667y + -0.8333333333z

Simplifying
x = 4.5 + 0.6666666667y + -0.8333333333z

See similar equations:

| -10x-21=-12x+31 | | 8x+4y+7z-4x+4z-5y= | | n+3.4=8.3 | | 4y-6(y+8)=8y+12 | | 7x^2-10*x-5=0 | | -5+6j=-53 | | -1x+3=19 | | 39=-3+5(x+6) | | 7w+8=64 | | 2x-5=-(3x+7) | | 3=-6x+3(x+3) | | 19-3x=9x-5 | | 1.8+7n=4n | | y+6=5x+3xr-4 | | 9-3p=3 | | 7x+-3=-11 | | 2-7x=5x+50 | | 2x=-(3x+7) | | 25m-10=21m+14 | | 10y-7=28+3y | | -122+2x=153-9x | | 8-3w=5 | | 3x-14=-5x+34 | | 16=7b+30 | | 0.70x=455000 | | 3u-12=-21 | | 4*7v= | | 8y-3=-27 | | 3z^2+3z+1=0 | | 2x^2-3x-72=0 | | 30y^2=36y | | 2(a-8)+7=5(a+2)-3a-29 |

Equations solver categories